Direct inhibition of factor VIIa by TFPI and TFPI constructs. Issue 4 (11th April 2013) - Peraramelli, S.; Thomassen, S.; Heinzmann, A.; Rosing, J.; Hackeng, T. M.; Hartmann, R.; Scheiflinger, F.; Dockal, M.
Summary Background Tissue factor pathway inhibitor (TFPI) is a multi‐Kunitz domain protease inhibitor that down‐regulates the extrinsic coagulation pathway by inhibiting FXa and FVIIa. Objectives To investigate the role of the three Kunitz domains (KDs) of TFPI in FVIIa inhibition using full‐length TFPI (TFPIfl) and truncated TFPI constructs. Methods Inhibition of FVIIa with/without relipidated tissue factor (TF) or soluble TF (sTF) by TFPIfl/TFPI constructs was quantified with a FVIIa‐specific chromogenic substrate. Results and Conclusions TFPIfl inhibited TF‐FVIIa via a monophasic reaction, which is rather slow at low TFPIfl concentrations (t½ ≈ 5 min at 2 nm TFPI) and has a Ki of 4.6 nm. In the presence of sTF and without TF, TFPIfl was a poor FVIIa inhibitor, with Ki values of 122 nm and 1118 nm, respectively. This indicates that phospholipids and TF significantly contribute to FVIIa inhibition by TFPIfl. TFPI constructs without the KD3‐c‐terminus (TFPI1–150 and KD1‐KD2) were 7–10‐fold less effective than TFPIfl in inhibiting TF‐FVIIa and sTF‐FVIIa, indicating that the KD3‐C‐terminus significantly contributes to direct inhibition of FVIIa by TFPI. Compared with KD1‐KD2, KD1 was a poor TF‐FVIIa inhibitor (Ki =434 nm), which shows that the KD2 domain of TFPI also contributes to FVIIa inhibition. Protein S stimulated TF‐FVIIa inhibition by TFPIfl (Ki =0.7 nm). In the presence of FXa, a tight quaternary TF‐FVIIa‐TFPI‐FXa complex is formed with TFPIfl, TFPI1–150 and KD1‐KD2, with Ki values of < 0.15 nm, 0.5 nm and 0.8 nm, respectively, indicating the KD3‐C‐terminus is not a prerequisite for quaternary complex formation. Phospholipids and the Gla‐domain of FXa are required for quaternary complex formation.